Tantangan dan Prospek Penguatan Sosial dan Budaya dalam Pembangunan Berkelanjutan yang Inklusif: Tantangan dan Prospek Penguatan Sosial dan Budaya dalam Pembangunan Berkelanjutan yang Inklusif - Mufidah; Reni Anggriani (UNIB Press, 2024)
This study examines the challenges and prospects of strengthening socio-culture in sustainable, inclusive development in Lekor Village, Central Lombok. Using a qualitative approach, this study identifies factors that influence the preservation of local culture amidst the flow of modernisation and economic pressures. The study results indicate that the younger generation is less involved in preserving culture, while the community faces the challenge of changing values ​​due to modernisation. However, there is great potential in developing culture-based tourism and the creative economy. Inclusive development involving the community, government, and the private sector is considered a solution to promote economic welfare without sacrificing cultural values. This study recommends improving culture-based education, tourism management skills training, and government policies that support the preservation of culture and community-based economy. Active participation of the community, especially the younger generation, is essential to maintain the sustainability of traditions while encouraging inclusive and sustainable economic development. In conclusion, despite many challenges, the existing opportunities can be optimally utilised through cross-sector collaboration and policies that support local culture.